Analisis Yuridis Tindak Pidana Perzinaan Berdasarkan Pasal 284 Kitab Undang-Undang Hukum Pidana Dalam Perspektif Hukum Pidana Dan Hukum Pidana Islam - Yudhistira Nugraha; Dessy Artina; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Pancasila as the basis, ideology, and philosophy of the nation consists of five precepts, the first andforemost precepts are the precepts of the One Godhead. the interpretation of Article 29 paragraph (1) of the1945 Constitution has six interpretations, three of which include the formation of law in Indonesia, everystatutory regulation in Indonesia must not conflict with Islamic law for Muslims including the inheritance ofthe Criminal Code (KUHP) The Netherlands contained in Article 284 of the Criminal Code concerningAdultery Crimes is contrary to the teachings of Islam. This study entitled